Peer support and learning outcomes in “Study With Me” among Generation Z college students: mediating roles of motivation, test anxiety, and self-efficacy - Rui Hou; Ling Jin; Jian He; Jin-Liang Wang (Frontiers in Psychology, 2025)
Background“Study With Me (SWM),” a popular trend among Generation Z college students, enabling self-directed learning through livestreams or prerecorded videos and offering peer support in virtual settings. However, its impact on learning outcomes remains underexplored.PurposeThis study examines how peer support impacts learning satisfaction and engagement in SWM, focusing on intrinsic motivation, extrinsic motivation, test anxiety, and self-efficacy as mediators, comparing livestreams and prerecorded formats.MethodsData were collected from 509 Chinese college students who had engaged in SWM on Bilibili for at least three consecutive months. Structural equation modeling (SEM) and multigroup analyses were conducted using SPSS 30.0 and AMOS 26.0.ResultsPeer support positively predicted intrinsic motivation, extrinsic motivation, self-efficacy, learning satisfaction, and engagement, and negatively predicted test anxiety. Intrinsic motivation, test anxiety, and self-efficacy mediated the effect of peer support on learning satisfaction, while intrinsic motivation, extrinsic motivation, and self-efficacy mediated its effect on learning engagement. Multigroup analysis revealed stronger peer support paths among livestream learners and stronger self-efficacy paths among prerecorded video learners.ConclusionThese findings underscore the importance of peer support in fulfilling psychological needs and improving learning outcomes in SWM, offering practical implications for enhancing digital learning and supportive online environments.